The Influence of Managerial Ownership and Firm Size On Debt Policy - Lihard Stevanus Lumapow (Journal of International Conference Proceedings (JICP), 2018)
This study aims to examine and analyze the effect of managerial ownership and firm size on debt policy in the perspective of agency theory. This research uses industrial samples of manufacturing companies listed on Indonesia Stock Exchange during 2012 until 2016. Sampling technique used is purposive sampling and data collection techniques are panel data (cross section and time series). While the analysis tool used in this research is panel data regression with fixed effect model (FEM) approach. Based on the test results show that managerial ownership has a positive and significant effect on debt policy. Company size has a negative but insignificant effect on debt policy. The results of this study have the potential for agency conflict. Keywords: Agency Conflict, Agency Theory, Debt Policy, Firm Size, Managerial Ownership